PENERAPAN DISIPLIN DALAM RANGKA PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL DI LINGKUNGAN SATUAN POLISI PAMONG PRAJA KOTA BOGOR - Rojak Rojak; Abubakar Iskandar; Beddy Iriawan Maksudi (LPPM Universitas Djuanda Bogor, 2015)
Government Regulation No. 53 of 2010 Concerning Servants Discipline is the legal basis to ensure civil servants and can be made the basis for the preparation of State apparatus that is good and right. Within the Civil Service Police Unit Bogor itself often occur pelanggaranber relation to breaches of discipline of civil servants, such as doing things that can degrade the honor or dignity of the State, the Government, or Civil Servants in this case many civil servants are absent from duty as law enforcement, entering places that can pollute the honor or dignity of civil servants, except for the sake of office, but violations are frequent delays often occur in the office of civil servants and absent without information on working hours Based on this background and the many issues concerning the discipline of civil servants. The authors formulate the problem of how the implementation of regulations under PP PNS Discipline 53 of 2010 on the Civil Service Police Unit in the city of Bogor, how sanctions applied against civil servants who do not obey the rules of discipline of civil servants, under PP 53 Year 2010 on the Civil Service Police Unit Bogor. Obstacles that arise in the implementation of the Disciplinary Code of civil servants under PP 53 Year 2010 on the Civil Service Police Unit Bogor. Research methods and approach used in the study was descriptive, with respect to the subject matter to be discussed is associated with the practice in the field in order to solve a problem by collecting and analyzing the data. The results of the field which penlis get is that the Civil Service Police Unit Bogor has been carried out since the PP is applied, until now, only one case relating to violations of discipline that PNS. In connection with the sanction given by the Civil Service Police Unit Bogor related violations by PNS PP 53 in 2010. While the constraints on the field in the context of the discipline of civil servants within the scope of the Civil Service Police Unit Bogor authors see it because it is influenced by several factors, such as lack of infrastructure, lack of awareness of the civil servants concerned, the lack of device and the rules of discipline and lack of guidance that is given by the Civil Service Police Unit Bogor. Keywords: Dicipline, Development, Work